Manejo Hospitalario de Cavia Porcellus y Oryctolagus Cuniculus Pasantía en la Clínica Veterinaria Animal Health Tetrapoda Pets (2023)
In recent years, the ownership of unconventional pets has become popular, which are called animals that do not have a specific purpose, but are adopted as companion animals (Alberto & Buitrago, 2017), among them are considered Cavia porcellus (guinea pigs) and Oryctolagus cuniculus (rabbit), for better animal care and well-being, more information is needed from professionals towards guardians of non-conventional pets.